A Critical Analysis of the Macroeconomic Policies in Brazil from Lula da Silva to Dilma Rousseff (2003-2014) - de Paula, Luiz Fernando; Ferrari, Fernando (Brazilian Keynesian Review, 2015)
In this short article, we aim at presenting a critical analysis of the macroeconomic policies implemented by the Lula da Silva and Dilma Rousseff governments in Brazil. The main hypothesis is that the economic framework of the ‘leftist’ governments has been managed pragmatically, mainly due to the global financial crisis (GFC) and the Great Recession (GR), and is still conservative, and cannot be considered as genuine Keynesian policies.